2016
DOI: 10.1093/mnras/stv2983
|View full text |Cite
|
Sign up to set email alerts
|

Bolometric light curves and explosion parameters of 38 stripped-envelope core-collapse supernovae

Abstract: Literature data are collated for 38 stripped-envelope core-collapse supernovae (SE SNe; i.e. SNe IIb, Ib, Ic and Ic-BL) that have good light curve coverage in more than one optical band. Using bolometric corrections derived in previous work, the bolometric light curve of each SN is recovered and template bolometric light curves provided. Peak light distributions and decay rates are investigated; SNe subtypes are not cleanly distinguished in this parameter space, although some grouping of types does occur and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

70
433
13
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(518 citation statements)
references
References 188 publications
70
433
13
2
Order By: Relevance
“…They showed that tight helium star-neutron star (NS) binary systems, presumably created in the common-envelope phase from high-mass X-ray binaries (Tauris & van den Heuvel 2006), can lead to the extreme stripping of the helium envelope and result in SNe with ejecta masses of the order of 0.1 M⊙ or less. The SN ejecta mass from these systems is even less than those typically obtained in SN progenitors from the first exploding stars (∼ 1 M⊙) during binary evolution (e.g., Yoon, Woosley, & Langer 2010;Lyman et al 2016a).…”
Section: Introductionmentioning
confidence: 73%
“…They showed that tight helium star-neutron star (NS) binary systems, presumably created in the common-envelope phase from high-mass X-ray binaries (Tauris & van den Heuvel 2006), can lead to the extreme stripping of the helium envelope and result in SNe with ejecta masses of the order of 0.1 M⊙ or less. The SN ejecta mass from these systems is even less than those typically obtained in SN progenitors from the first exploding stars (∼ 1 M⊙) during binary evolution (e.g., Yoon, Woosley, & Langer 2010;Lyman et al 2016a).…”
Section: Introductionmentioning
confidence: 73%
“…Recently, Smith (2014) challenged the established picture of single-star mass loss; namely, that mass loss through conventional line-driven winds should not be sufficient to create a type Ib/c SN, and most of their progenitors should be stripped through binary interaction. Lyman et al (2016) found the ejecta masses of type Ib/c and IIb SNe inconsistent with very massive stars, also indicating that interacting binaries are the dominant progenitor channel. The effects of multiplicity on massive star evolution, however, are not well understood either, despite its tremendous importance (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…Massive progenitors of M f > 8 M ⊙ would result in too broad light curves compared to those of ordinary SNe Ic (e.g., Dessart et al 2017). Studies on SN light curves and spectra indicate that ordinary SNe Ic have ejecta masses less than about 5-6 M ⊙ (e.g., Drout et al 2011;Cano 2013;Taddia et al 2015;Lyman et al 2016), except for some extreme cases like iPTF15dtg (M ejecta ≈ 10 M ⊙ ; Taddia et al 2016). In this regard, our result with f WR = 1.58, which predicts M f 5 M ⊙ for SN Ic progenitors, is in better agreement with observations than those with the NL prescription.…”
Section: Implications For Sn Ib/ic Progenitorsmentioning
confidence: 99%